(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This paper focuses on the relationship between Cervantes’ Cart of Death episode (Quijote, II, 11) and the sacramental play entitled Las Cortes de la Muerte (The Parliament of Death), usually attributed to Lope de Vega. This play has received some attention by the critics because it is almost certainly the sacramental play mentioned in the second part of Don Quixote, when the knight-errant meets the actors belonging to the Angulo el Malo’s company. After commenting on Cervantes’ episode and the possible identification of the sacramental play mentioned there, the paper provides a dramatic and literary analysis of Las Cortes de la Muerte (The Parliament of Death), with comment about its structure and other details concerning its allegorical and symbolic constructions.